Ideal portfolio construction by using single index model based on bursa Malaysia data / Sidi Syaffiee Sidi Omar - Sidi Omar, Sidi Syaffiee (Universiti Teknologi Mara Kampus Kota Bharu, 2015)
The main purpose of this paper is to construct an ideal portfolio by using one of the model which is Sharpe's single-index model. For this purpose the daily closing prices of 686 companies listed in Main Market in Bursa Malaysia and all share price index for the period of September 2009 to September 2014 have been considered. The proposed method formulates a unique cut off point (Cut off rate of return), selects stocks having excess return to beta ratio surpassing this cut off point, and determines the percentage of investment in every of selected stocks. The optimum portfolio consists of 189 stocks selected out of 686stocks, giving the return of 0.26%.